THREE LITTLE WORDS BY JESSICA THOMPSON: AN ANNOTATED TRANSLATION - Sabrina, Adani Nur (Universitas Gunadarma, 2017)
This research is an annotated translation with the novel Three Little Words by Jessica Thompson as its source of the data. The purposes of this research are to acquire objective information of the difficulties emerged during the process of translation and to present the solutions to the difficulties. The methods used by the researcher are retrospective and introspective methods. The result of the research showed that the 5 chosen data to be analyzed used the following translation strategies: transposition, coherence change, loan, paraphrase, and calque.Keywords: Translation, annotated translation.